Asymmetric Behavior of Thymidylate Synthase Dimer Subunits in Denaturating Solvent Observed with Molecular Dynamics. (11th March 2015) - Leonarski, Filip; Świniarska, Monika; Leś, Andrzej
Abstract : A molecular dynamics simulations of the thymidylate synthase denaturation in chaotrope solvents (urea, guanidinium hydrochloride) were performed on 600 ns timescale. It appeared that this dimeric enzyme undergoes partial unfolding asymmetrically. It was shown also that urea is a better denaturant in the MD condition, as compared to guanidinium chloride. The unfolding occurs first at the external helices (AA 88-118) and follows by the AA 188-200 region. The present results correspond to the suggested in the literature activity of thymidylate synthase through a half-the-site mechanism.